2021
DOI: 10.15252/embr.202051280
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 is activated by platinum and contributes to cisplatin‐induced ototoxicity

Abstract: Toll-like receptor 4 (TLR4) recognizes bacterial lipopolysaccharide (LPS) and can also be activated by some Group 9/10 transition metals, which is believed to mediate immune hypersensitivity reactions. In this work, we test whether TLR4 can be activated by the Group 10 metal platinum and the platinum-based chemotherapeutic cisplatin. Cisplatin is invaluable in childhood cancer treatment but its use is limited due to a permanent hearing loss (cisplatin-induced ototoxicity, CIO) adverse effect. We demonstrate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Thus, chronic unregulated and unresolving TLR activation may be responsible for immunopathological consequences, as augmented TLR-induced inflammation and increased expression have been reported in a plethora of non-\infectious and autoimmune diseases that target the renal system, including nephrotoxicity [214]; renal disease [56,215,216]; lupus nephritis [202]; and diabetic nephropathy [217]. Furthermore, TLRs have also been implicated as potential drivers of cisplatin-induced pathologies and toxicities, including AKI [55,218,219]; renal injury [220][221][222]; allodynia [218]; and ototoxicity [223]. As demonstrated by TLR-deficient animal models [55,218,219] and polymorphisms in humans [224][225][226][227], the absence or improper function of TLRs may influence susceptibility and severity of pathologies affecting the renal system.…”
Section: Toll-like Receptors and Cisplatin-induced Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, chronic unregulated and unresolving TLR activation may be responsible for immunopathological consequences, as augmented TLR-induced inflammation and increased expression have been reported in a plethora of non-\infectious and autoimmune diseases that target the renal system, including nephrotoxicity [214]; renal disease [56,215,216]; lupus nephritis [202]; and diabetic nephropathy [217]. Furthermore, TLRs have also been implicated as potential drivers of cisplatin-induced pathologies and toxicities, including AKI [55,218,219]; renal injury [220][221][222]; allodynia [218]; and ototoxicity [223]. As demonstrated by TLR-deficient animal models [55,218,219] and polymorphisms in humans [224][225][226][227], the absence or improper function of TLRs may influence susceptibility and severity of pathologies affecting the renal system.…”
Section: Toll-like Receptors and Cisplatin-induced Acute Kidney Injurymentioning
confidence: 99%
“…Furthermore, TLR4 can respond to a broad range of DAMPs, including endoplasmin [239], high-mobility group-1 [246], and heat-shock protein 70 [247], which have been shown to be upregulated during cisplatin treatment. Interestingly, TLR4 has also been shown to participate in transition metal sensing [248], and metals, including nickel, cobalt, and platinum [223,248] have been observed as TLR4-activating ligands. Due to the increase in circulating DAMPs and cisplatin (a platinum-based chemotherapy) acting as TLR4 ligands, TLR4 has been implemented as a major contributor in driving pathogenesis and development of CIAKI through upregulation of inflammation and proinflammatory and subsequent renal dysfunction, renal tissue injury, and nephrotoxicity [239].…”
Section: Toll-like Receptor 4 Has a Detrimental Role In Cisplatin-indmentioning
confidence: 99%
“…On the other hand, numerous studies exist indicating that cisplatin-induced proinflammatory responses can develop even in presumptively sterile conditions and in an MD2-independent manner. In 2021, Babolmorad et al demonstrated that cisplatin-induced pro-inflammatory cytokine secretion could be induced in human embryonic kidney cells that express TLR4 but do not express MD2 [78]. The inhibition of TLR4 activation through commercially available chemical inhibitors like TAK242, and the prevention of TLR4 expression through siRNA and clustered regularly interspaced short palindromic repeats (CRISPR), all proved sufficient to reduce CIT-associated proinflammatory responses in the same system [78].…”
Section: Pattern Recognition Receptors (Prrs) In Cisplatin-induced To...mentioning
confidence: 99%
“…In 2021, Babolmorad et al demonstrated that cisplatin-induced pro-inflammatory cytokine secretion could be induced in human embryonic kidney cells that express TLR4 but do not express MD2 [78]. The inhibition of TLR4 activation through commercially available chemical inhibitors like TAK242, and the prevention of TLR4 expression through siRNA and clustered regularly interspaced short palindromic repeats (CRISPR), all proved sufficient to reduce CIT-associated proinflammatory responses in the same system [78]. Moreover, it was also demonstrated that TLR4 may specifically interact with the platinum component of cisplatin to mediate inflammation as it has been shown to do so for metal allergens, suggesting that potentially direct interactions between cisplatin and TLR4 could be stimulating CIO; however further evidence is required to confirm this.…”
Section: Pattern Recognition Receptors (Prrs) In Cisplatin-induced To...mentioning
confidence: 99%
“…Cisplatin is a chemotherapy agent used for the first-line treatment of the majority of cancer patients [1]. Although clinical trials have shown effectiveness, unfavorable cytotoxic side effects are a huge hurdle that impedes the clinical application of otherwise beneficial cisplatin-based treatments [2][3][4]. Intestinal mucositis, a serious chemotherapy-induced side effect, is characterized by local accumulation of inflammatory cells [5], cell loss in the epithelial barrier [6], increased oxidative stress [7], and reduced gastrointestinal digestive enzyme activities [8].…”
Section: Introductionmentioning
confidence: 99%